Detecting slow-translating regions in E.coli. (11th January 2011) - Ponnala, Lalit
We present an application of the spatial scan statistic to identifying clusters of slow-translating codons in E.coli. We use an estimate of the time taken to process each codon based on the availability of transfer RNA. We analyse our findings using experimental measurements, and provide support for a well-known hypothesis related to the process of protein production.